1996
DOI: 10.1046/j.1365-2036.1996.22164025.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine modulation by glucocorticoids: mechanisms and actions in cellular studies.

Abstract: Glucocorticoids inhibit the expression and action of most cytokines. This is part of the in vivo feed-back system between inflammation-derived cytokines and CNS-adrenal produced corticosteroids with the probable physiological relevance to balance parts of the host defence and anti-inflammatory systems of the body. Glucocorticoids modulate cytokine expression by a combination of genomic mechanisms. The activated glucocorticoid-receptor complex can (i) bind to and inactivate key proinflammatory transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
194
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(211 citation statements)
references
References 4 publications
11
194
1
5
Order By: Relevance
“…This is in agreement with previous studies showing that steroids broadly attenuate cytokine production not only of pro-inflammatory TNF␣, but also of the anti-inflammatory IL-10. 24 Interestingly, we observed that 5-ASA usage was associated with higher IL-10 secretion and like smoking could therefore act through a feedback control.…”
Section: Discussionmentioning
confidence: 84%
“…This is in agreement with previous studies showing that steroids broadly attenuate cytokine production not only of pro-inflammatory TNF␣, but also of the anti-inflammatory IL-10. 24 Interestingly, we observed that 5-ASA usage was associated with higher IL-10 secretion and like smoking could therefore act through a feedback control.…”
Section: Discussionmentioning
confidence: 84%
“…The pathogenic mechanisms in patients with HLA DR4 may be more dependent on cytokines modified by corticosteroid therapy than patients with HLA DR3. 40,41 Alternatively, the responsiveness of the elderly to corticosteroid therapy may reflect in part age-related changes in immune reactivity. Aging alters immune responsiveness by decreasing the expression of HLA class II molecules 42 and reducing stimulation and proliferation of antigen-stimulated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the relatively low concentration of cycloheximide used (1 mg ml 21 ) in our experiments, translation of the superinduced transcripts may not be completely abolished, thus explaining such increases in the protein amounts. As cycloheximide exposure had little effect in abolishing cytokine release by C. trachomatis-infected HeLa cells, infected cultures were subsequently examined, especially for IL-11 and IL-6 production, following exposure to dexamethasone, a glucocorticoid known to modulate cytokine production (Brattsand and Linden, 1996;Wang et al, 1999). At a concentration of 10 26 M, dexamethasone induced a dramatic decrease in IL-8 (71% reduction), IL-11 (97% reduction) and IL-6 (95% reduction) release by L2-infected cells compared with unexposed infected cells (Table 3).…”
Section: Effect Of Inhibitors On Cytokine Release By C Trachomatisinmentioning
confidence: 99%